2021
DOI: 10.1051/epjpv/2021003
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigations of the impact of buffer germanium composition and low cost fabrication of Cu2O on AZO/ZnGeO/Cu2O solar cell performances

Abstract: Numerical simulations of AZO/Zn1−xGexO/Cu2O solar cell are performed in order to model for the first time the impact of the germanium composition of the ZnGeO buffer layer on the photovoltaic conversion efficiency. The physical parameters of the model are chosen with special care to match literature experimental measurements or are interpolated using the values from binary metal oxides in the case of the new Zn1−xGexO compound. The solar cell model accuracy is then confirmed thanks to the comparison of its pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Modeling has been performed on all-oxide solar cells comprising Cu 2 O as the main absorber. 17−20 Different structures, i.e., (AZO/ZnGeO/Cu 2 O), 21 (ZnO/CuO/ Cu 2 O), 19 and (AZO/ZnO/defective layer/Cu 2 O), 22 have been studied to understand the various mechanisms taking place. However, the main focus is commonly on simulating Cu 2 O thin films combined with several layers (i.e., buffer, tandem, and transparent conductive oxides) 17−19,22−25 or on the analysis of optical properties of Cu 2 O-based solar devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling has been performed on all-oxide solar cells comprising Cu 2 O as the main absorber. 17−20 Different structures, i.e., (AZO/ZnGeO/Cu 2 O), 21 (ZnO/CuO/ Cu 2 O), 19 and (AZO/ZnO/defective layer/Cu 2 O), 22 have been studied to understand the various mechanisms taking place. However, the main focus is commonly on simulating Cu 2 O thin films combined with several layers (i.e., buffer, tandem, and transparent conductive oxides) 17−19,22−25 or on the analysis of optical properties of Cu 2 O-based solar devices.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling has been performed on all-oxide solar cells comprising Cu 2 O as the main absorber. Different structures, i.e., (AZO/ZnGeO/Cu 2 O), (ZnO/CuO/Cu 2 O), and (AZO/ZnO/defective layer/Cu 2 O), have been studied to understand the various mechanisms taking place. However, the main focus is commonly on simulating Cu 2 O thin films combined with several layers (i.e., buffer, tandem, and transparent conductive oxides) , or on the analysis of optical properties of Cu 2 O-based solar devices. , Previous experimental studies have already shown that film thickness, band alignment, and defects (both affected by the deposition method and conditions used) are the main factors affecting cell performance. ,, One of the main achievements of these results is the improvement of the cell efficiency with different structures through introducing different interfaces and defective layers at the junction interface. ,, Other studies combining experimental and simulation results have addressed in depth the impact of film defects on the quantum efficiency of cells. , The latter have shown that the external quantum efficiency (EQE) of Cu 2 O-based solar cells changes drastically with the type of defects (interfacial or bulk) and interface roughness. , Various software have been used for simulating Cu 2 O-based solar cells, mainly SCAPS-1D, ,, wxAMPS, ,, and Silvaco TCAD .…”
Section: Introductionmentioning
confidence: 99%
“…List of input variables from available literature[16,21,26]. Capture cross section [cm 2 ] 5 × 10 -13 /1 × 10 -15 5 × 10 -13 /1 × 10 −15 1 × 10 −12 /1 × 10 −15…”
mentioning
confidence: 99%